The effects of lead on the growth, reproduction & behaviour of three earthworm species: Eisenia fetida, Eudrilus eugeniae and Perionyx excavatus (Oligochaeta) - Maboeta, Mark Steve (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1997.